1990
DOI: 10.1002/cjce.5450680218
|View full text |Cite
|
Sign up to set email alerts
|

Hydrolysis of carbonyl sulfide: Comparison to reactions of isocyanates

Abstract: The hydrolysis of carbonyl suflfide (COS), catalyzed by tertiary amines, was studied in a gas‐liquid reactor at ambient conditions. Rate constants determined in a batch reactor were similar to those determined in a continuous flow reactor. A Bronsted plot of the reaction data over the amine basicity range, 0 < pKB < 14, suggested that both amine basicity and steric factors determine catalytic behavior. The reaction data suggest a mechanism analogous to one used to explain the base catalyzed reaction of isocyan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 9 publications
0
16
0
Order By: Relevance
“…-COS & comparison to the more common tertiary alkanolamines (Ernst and Chen, 1988;Ernst et al, 1990; R e i y et al, 1990).…”
Section: Literaturementioning
confidence: 99%
“…-COS & comparison to the more common tertiary alkanolamines (Ernst and Chen, 1988;Ernst et al, 1990; R e i y et al, 1990).…”
Section: Literaturementioning
confidence: 99%
“…Ernst and Chen (1988) reported absorption data for COS into solutions consisting of a heterocyclic amine (e.g. The observations presented by Ernst et al (1990) for solutions of various heterocyclic amines were analogous to those reported by Ernst and Chen (1988). The heterocyclic amines studied by Ernst and Chen (1988) were claimed to show substantially higher activity in COS hydrolysis than common tertiary alkanolamines at about the same base strength.…”
Section: Literaturementioning
confidence: 68%
“…In addition, Ernst and co-workers considered whether cyclic tertiary amines could catalyze the hydrolysis reaction of COS: A cyclic tertiary amine (denoted as “CTA”) reacts with COS to form an active intermediate (denoted as “complex”) which subsequently hydrolyzes fast to form H 2 S, CO 2 , and the cyclic tertiary amine. The intermediate formation described by eq 6 is the rate-determining step for the overall reaction.…”
Section: Resultsmentioning
confidence: 99%
“…Ernst et al and Reilly et al. investigated the reaction kinetics of several cyclic amines with COS; the results show that the reaction rates of 1,4-diazabicyclo[2.2.2]­octane (DAB), quinuclidine and 1,5-diazabicyclo[4.3.0]­non-5-ene (DBN) are dozens of times as much as that of MDEA.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation